GENETIC SIMILARITIES BETWEEN UKRAINIAN BLACKSPOTTED MILK AND HOLSHTAIN BREEDS ACCORDING TO THE GENUS BOLA-DRB 3.2 - Супрович, Т. М.; Супрович, М. П.; Копилов, К. В.; Колінчук, Р. В. (Podilian Bulletin: Agriculture, Engineering, Economics, 2017)
DNA markers using to assess the genetic variation. In cattle second exon of gene BoLA-DRB3 is highly polymorphic; allowing the use of its alleles to determine genetic diversity. To increase milk production Ukrainian Black Pied dairy cattle is widely used hereditary material Holstein breed. In their study; we revealed allelic spectrum for gene BoLA-DRB3.2. His comparing with fund of alleles Holstein and holstein breeds we can use to set the genetic similarity of populations of cattle; evaluate the direction and its accuracy. The study performed at the breeding farm "Cossack Valley 2006". Here intensive carry out selection using semen of bulls Holstein. Experiments conducted at intervals of five years; respectively: 2010 (162 heads) and 2015 (114 heads). The allelic spectrum of gene BoLA-DRB3.2 detected by means of two-step (HLO-30 primers; HLO-31 and HLO-32) and allele-specific PCR. Restriction executed by endonucleases RsaI; Hae III and Bst YI. Received fragments separated by electrophoresis in 4% agarose gel. For the analysis determined the frequency of alleles; genetic distance and similarity. Statistical treatment and cluster analysis for building dendrograms performed in the standard package Microsoft Excel and integrated program Statisti XL 2.0. The consequences of Holstein selection detected by comparing the genetic distances eleven populations Holstein and holstein cattle other countries; which are calculated based on allele frequencies. The selection measures over the last five years have led the emergence in genotype of cow’s new four alleles: * 06 * 14 * 19 and * 51. There is accumulation of "informative" alleles specific to Holstein * 16 (from 0;62 to 5;26%) and * 24 (from 11.7 to 18%) and the elimination of allele * 22 (from 12 to 7;89%). Between 2010 and 2015 in herds appeared a genetic difference (D = 0;081). At the same time is increasing the genetic relationship of populations of 2015 and Holstein and holstein breeds other countries. This confirmed by the growth of genetic similarity between populations compared with data for the herds studied in 2010 and dendrograms; building based on cluster analysis of genetic distances. The research and comparisons confirm positive breeding measures using Holstein. However; currently Ukrainian black-pied dairy breed retains a significant level of genetic diversity